ANALYSIS OF RISK FACTORS FOR OBESITY IN WOMEN AGED 15-49 YEARS IN SOUTH AFRICA (THE DHS PROGRAM 2016) - Sinatrya, Alfadhila Khairil; Mahmudiono, Trias; Melaniani, Soenarnatalina (Universitas Airlangga, 2023)
Overweight and obesity can be interpreted as abnormal fat accumulation that can cause health problems. The average BMI (Body Mass Index) in adult women has also continued to increase. This study aims to identify the relationship between age, alcohol consumption, cigarette consumption, employment status, economic status, ethnicity and area of